Relasi Kuasa Dalam Tataniaga Pertanian Komoditas Cabai di Desa Giri Mulyo, Kabupaten Kerinci, Jambi - Wibi Wijaya (Indonesian Journal of Religion and Society, 2020)
Giri Mulyo village of West Kayu Ayo district was known as the biggest the biggest chilli-producing village in Kerinci Regency.  In addition, this village also produce the commodity of potatoes and other agricultural products such as shallots, cabbage, mustard greens, tomatoes, and other types of vegetables which are marketed to various regions. The purpose of this research was to investigate the commerce and authority relations formed between chilli farmers and chilli merchants. This reseach conducted qualitatively through observation, deep interview and document study to collect desired data. The result of study showed that in terms of commodity price, the farmers were dependant to merchant decision, and in fact they sometimes suffered losses. Moreover, the chilli farmers especially the sharecroppers sold their product to merchants because they had been their old clients. This relation was maintained because the farmers and the sharecroppers usually depended on them in running their farming business. Furthermore, the authority relation formed between the parties was also influenced by factors of culture, farmer’s helplessness, and market situation.